Physical activity and exercise in youth mental health promotion: a scoping review. Issue 1 (23rd January 2020) - Pascoe, Michaela; Bailey, Alan P; Craike, Melinda; Carter, Tim; Patten, Rhiannon; Stepto, Nigel; Parker, Alexandra
Abstract : Background/Aim: This scoping review examined the breadth and outcomes of controlled trials testing the effect of physical activity and exercise interventions across all mental health outcomes for mental health promotion and indicated prevention studies in young people. Methods: The literature search was conducted using 'Evidence Finder'. Results: Thirty publications were included. Available evidence suggested that interventions of varying intensity may lead to a reduction in depression symptoms and that moderate-to-vigorous-intensity and light-intensity interventions may reduce anxiety symptoms. Effects of physical activity/exercise interventions on additional mental health outcomes were also shown; however, the number of studies was small, indicating a limited evidence base. Robust research regarding the effects of physical activity/exercise on mental health promotion and as an indicated prevention strategy in young people is lacking. Conclusion: The available evidence suggests that physical activity/exercise is a promising mental health promotion and early intervention strategy and warrants further investigation.